Industri dan Supply Chain Halal dilihat dari Aspek Keilmuan Teknik Industri - Iwan Satriyo Nugroho; Tombak Gapura Bhagya; Dian Rosinawati (Universitas Insan Cendekia Mandiri, 2020)
The potential for the Halal Industry is enormous, both for foreign and domestic needs in Indonesia. The need for commodities with halal guarantees for Muslim countries, even in non-Muslim majority countries, continues to increase from year to year, in the form of foodstuffs, medicines and cosmetics. From 2017 to 2018 it grew to 5.1%, reaching 1.37 trillion dollars in 2018. However, Indonesia is still a consumer and not a producer. Various challenges in the halal industry and supply chain as well as challenges in the Islamic economy as a support for the halal industry become an analysis of the causes of Industrial Engineering Science with its various scientific tools can be the answer to some problems. This research will explain about the Halal Industry and Supply Chain from the scientific aspects of Industrial Engineering which includes facts and data on the halal sector, regulations and sharia economics as a support for the halal industry, the halal food sector, halal operations, halal logistics (supply chain). ) and the potential of the halal industry in Indonesia.